Polymer-Related Anomalies and Findings in Solarparks - A Starting Point for Adapted Test Sequences - Buerhop, Claudia; Stroyuk, Oleksandr; Mashkov, Oleksandr; Winkler, Thilo; Hauch, Jens; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2024)
In this comprehensive study, we present a synthesis of our extensive observations on backsheet (Bsh) faults and degradation patterns, gathered through meticulous inspections conducted over several years in solar parks. Our investigation provides valuable insights into the distribution and accumulation of visual anomalies, offering crucial statements of their impact on system performance, operational efficiency, and overall service life. The primary focus of our research centers on the identification of polymer-related anomalies. We strive to uncover correlations among diverse factors, including the year of commissioning, module manufacturer, Bsh type, and visual alterations. Our meticulous analysis encompasses 90,749 PV modules, equivalent to approximately 23 MWp) representing an average of 9% of the total installed PV modules across the 13 solar plants under evaluation. A significant observation emerges from the study, revealing that 22.5% of the characterized PV modules display optically detectable anomalies associated with polymers. These anomalies manifest as signs of material degradation and aging, presenting with varying degrees of significance. The observed issues range from subtle yellowing to more severe manifestations, such as the loss of insulation resistance. This study contributes to the understanding of Bsh-related challenges in solar installations, providing stakeholders with key insights to enhance system reliability and longevity.
CRIS-Team Scopus Importer:2025-02-04